Clinicopathological Characteristics of PIRADS 3 Prostate Lesion: A Retrospective Study - Thapa, Bikash Bikram; Basnet, Bina; Karki, Gaurav; Thapa, Narayan (The Surgery Journal, 2025)
Prostate carcinoma is the most common carcinoma in male. The evaluation of the suspected prostate carcinoma is based on the abnormal digital rectal examination, raised serum prostate specific antigen (PSA), followed by prostate biopsy with or without magnetic resonance imaging (MRI). The Prostate Imaging-Reporting and Data System (PIRADS) uses five-point scale (1–5), and is a global standard image acquisition, interpretation, and reporting protocol providing clinical guidelines for the management of the prostate carcinoma. PIRADS 3 is considered equivocal or intermediate risk for prostate carcinoma. The management of PIRADS 3 lesions without missing the clinically significant carcinoma and avoiding unnecessary biopsies has been a challenge to urologists. The aim of this study is to evaluate the clinicopathological characteristics, and to find out the incidence of clinically significant prostate carcinoma (csPCa) in PIRADS 3 lesion.It is a retrospective study where patients who underwent transrectal ultrasound (TRUS) guided biopsy of prostate for PIRADS 3 lesion diagnosed in multiparametric MRI (mpMRI) from October 2019 to December 2024 were reviewed and data collected for analysis.During the study period 19% (n = 34/178) had PIRADS 3 lesion. Patients with PIRADS 3 lesion had a mean age of 67 ± 8 years (mean ± standard deviation). About 41% (n = 14/34) of PIRADS 3 prostate lesion had acinar adenocarcinoma of prostate, and 20.5% (7 out of 34) had csPCa. All the csPCa cases had mpMRI lesion size of >10 mm and PSA density >0.2 ng/mL/cc.There is a significant risk of prostate carcinoma (41%) among the PIRADS 3 prostate lesion. Further evaluation and management of the PIRADS 3 lesion should be based on risk stratification based on index lesion size and PSA density.
Keywords: prostate carcinoma; PIRADS; mpMRI of prostate; prostate specific antigen